More N fertilizer, more maize, and less alfalfa: maize benefits from its higher N uptake per unit root length - Shao, Zeqiang; Zheng, Congcong; Postma, Johannes Auke; Gao, Qiang; Zhang, Jinjing (Frontiers in Plant Science, 2024)
Root plasticity is fundamental to soil nutrient acquisition and maximizing production. Different soil nitrogen (N) levels affect root development, aboveground dry matter accumulation, and N uptake. This phenotypic plasticity is well documented for single plants and specific monocultures but is much less understood in intercrops in which species compete for the available nutrients. Consequently, the study tested whether the plasticity of plant roots, biomass and N accumulation under different N levels in maize/alfalfa intercropping systems differs quantitatively. Maize and alfalfa were intercropped for two consecutive years in large soil-filled rhizoboxes and fertilized with 6 different levels of N fertilizer (0, 75, 150, 225, 270, and 300 kg ha-1). Root length, root surface area, specific root length, N uptake and yield were all increased in maize with increasing fertilizer level, whereas higher N rates were supraoptimal. Alfalfa had an optimal N rate of 75-150 kg ha-1, likely because the competition from maize became more severe at higher rates. Maize responded more strongly to the fertilizer treatment in the second year when the alfalfa biomass was much larger. N fertilization contributes more to maize than alfalfa growth via root plasticity responses. Our results suggest that farmers can maximize intercropping yield and economic return by optimizing N fertilizer management.